The Effect of Job Satisfaction and Compensation on Employee Turnover Intention in Companies PT Hadji Kalla Branch Urip Sumoharjo - Wahyudi, Andi Muh Fadhil; Hasbiah, Siti; Sahabuddin, Romansyah; Burhanuddin; Natsir, Uhud Darmawan; Aswar, Nurul Fadilah (PT. Maju Malaqbi Makkarana, 2023)
The purpose of this study was to determine the effect of Job Satisfaction and Compensation on Turnover Intention at PT Hadji Kalla Urip Sumoharjo Branch, Panakkukang District, Makassar City, the subjects in this study were 51 employees working at PT Hadji Kalla Urip Sumoharjo Branch. This research is included in quantitative research and quantitative analysis to test the research hypothesis using the IMB SPSS version 25 software. The results of this study indicate that job satisfaction has a negative and significant effect on turnover intention. This is evidenced by the t value of -3.055 where <t table (2.00958) and a significance value of 0.004 <0.05. The results of the study show that compensation has no significant effect on turnover intention. This is evidenced by the t value of 0.615 < t table (2.00958) and a significance value of 0.541 > 0.05. The results of the study show that job satisfaction and compensation have a simultaneous effect on turnover intention. This is evidenced by the calculated F value of 11.859 > 3.19 and a significance value of 0.001 <0.05.